Tailored nanofiltration membranes with enhanced permeability and antifouling performance towards leachate treatment - Pu, Liangtao; Xia, Qiancheng; Wang, Yanfeng; Bu, Yongguang; Zhang, Quanxing; Gao, Guandao (Journal of membrane science, 2022)
The leachate generated from the sanitary landfill or incineration poses serious environmental threats and it's difficultly disposed due to its complexity containing high concentration of organic matters and inorganic salts etc. Membrane technology stands out as a potential solution for leachate because of its beneficial advantages. Nanofiltration (NF) can reject organic compounds and separate divalent ions from mixed salts, which alleviates fouling and increases separation efficiency and flux of reverse osmosis (RO) in the popular combined processes (MBR-NF/RO) applicable for leachates. However, NF is often subject to low water permeance and membrane fouling for traditional polyamide thin film composite (PA-TFC) membranes. This work develops a high-performance NF membrane by grafting bipyridinium derivative monomer (BBD), an alternative antibacterial by interfering with the bacterial metabolism and reproduction and a hydrophilic compound endowing membrane hydrophilicity, onto PA-TFC membranes through the esterification reaction toward the leachate treatment. Resultantly, the BBD-TFC membrane achieves a reasonably high pure water permeability of 31.6 ± 2.1 L m−2 h−1 bar−1, ∼ 4 times higher than that of the pristine polyamide membrane. Notably, the resultant membrane exhibits excellent antifouling and antibacterial properties in the treatment of the leachate benefiting from the more hydrophilic surface and negative potential on BBD-TFC. Meanwhile, high rejection ratio of divalent ions and organic matter (R > 95%) was also attained companying with high separation efficiency of divalent/monovalent ions. The current work may provide an effective strategy to design high performance NF membranes for the leachate treatment or other wastewater treatment. [Display omitted] •TFC NF membranes grafted by bipyridinium derivative monomer (BBD) was developed.•Water flux of BBD-TFC was ∼ 4 times higher than that of the pristine TFC membrane.•BBD-TFC exhibited excellent antifouling and antibacterial properties toward leachate treatment.•Organic matter was highly retained companying with high separation of mono/divalent ions.